B-Tri Recycle: Magis Ramah Lingkungan yang Menyegarkan Desa Nagrog dari Masalah Sampah - Hayatunufus, Zakia (Lentera Karya Edukasi, 2024)
Abstract: Garbage is an environmental problem that is closely related to population size, consumption levels, and public awareness of the importance of protecting the environment. This has become one of the problems in Nagrog Village. The B-Tri Recycle program carried out by the 2023 UPI Thematic Community Service Group aims to reduce the amount of waste and environmental pollution in Nagrog Village. The methods used were environmental observations and interviews with staff and villagers. This program produced 8 trash cans, consisting of 6 trash cans made from used plastic bottles and 2 trash cans made from bamboo. This program received a positive response from the village and the local community.